2015
DOI: 10.1111/anae.13331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anaesthesia on proliferation, invasion and apoptosis of LoVo colon cancer cells in vitro

Abstract: Tumour cell proliferation, invasion and apoptosis are crucial steps in tumour metastasis. We evaluated the effect of serum from patients undergoing colon cancer surgery receiving thoracic epidural and propofol anaesthesia on colon cancer cell biology. Patients were randomly assigned to receive propofol anaesthesia with a concomitant thoracic epidural (PEA, n = 20) or sevoflurane anaesthesia with opioid analgesia (SGA, n = 20). Venous blood was obtained before induction of anaesthesia and 24 hours postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 37 publications
1
69
1
1
Order By: Relevance
“…Multimodal analgesia is critical both to ERAS and to achieve the target of DREAMing (DRinking, EAting and Mobilising) . Regional anaesthesia complements and enhances multimodal analgesia for abdominal surgery, with its role increasingly recognised , and may indeed alter outcomes . However, which regional anaesthetic technique is most appropriate, efficacious, safe, timely and consistent in the hands of most practitioners remains highly debated.…”
Section: Problemsmentioning
confidence: 99%
“…Multimodal analgesia is critical both to ERAS and to achieve the target of DREAMing (DRinking, EAting and Mobilising) . Regional anaesthesia complements and enhances multimodal analgesia for abdominal surgery, with its role increasingly recognised , and may indeed alter outcomes . However, which regional anaesthetic technique is most appropriate, efficacious, safe, timely and consistent in the hands of most practitioners remains highly debated.…”
Section: Problemsmentioning
confidence: 99%
“…We found that propofol had little inhibitory effect on the glucose metabolism of normal cells. Previous studies showed that propofol deceases the metastasis and progression of many cancers, including pancreatic cancer [26], breast cancer [27], colon cancer [28], gastric cancer [22], and cervical cancer [29]. However, the specific role of propofol in glucose metabolism in cancer cells remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal analgesia is critical both to ERAS [2] and to achieve the target of DREAMing (DRinking, EAting and Mobilising) [7]. Regional anaesthesia complements and enhances multimodal analgesia for abdominal surgery, with its role increasingly recognised [8], and may indeed alter outcomes [9][10][11]. However, which regional anaesthetic technique is most appropriate, efficacious, safe, timely and consistent in the hands of most practitioners remains highly debated.…”
Section: Problemsmentioning
confidence: 99%